Tinjauan Sosiologi Sastra dalam Novel Anak Ms.Hannah yang Suka Koleksi Sampah Karya D.Gutman serta Relevansinya terhadap Bahan Ajar Sastra di SD - Annisa Dinda Hapsari; Ezik Firman Syah (Journal on Education, 2023)
The problem in this study is that the teacher only provides literature teaching materials that are already available in theme books, resulting in a lack of student experience in understanding literary works in Indonesian language learning. This research aims to analyze a review of the sociology of literature in Ms. D. Gutman and to find out its relevance to literature teaching materials in elementary school. This study uses a type of qualitative research, with content analysis methods. Data collection techniques in this study used observation, interviews, and documentation. The data source was obtained from the children's novel Ms.Hannah Who Likes Garbage Collection by D.Gutman. The research results obtained show that there are four sociological aspects, namely social aspects, economic aspects, educational aspects, and moral aspects. Ms.'s children's novel Hannah Who Loves Garbage Collection by D. Gutman fulfills the criteria of teaching materials that are appropriate for use and educate readers. There is an intrinsic element in the novel as well as a support that can be used when studying literature in class. Thus, Ms.'s children's novel. Hannah Who Loves Garbage Collection by D. Gutman is relevant to literature teaching materials in elementary schools. Teachers as educators as well as teachers should be more selective in providing good reading materials for students and be careful in choosing teaching materials that will be used as examples of learning in class.